Poligami Menurut Perspektif Normatif Dan Realita Sosial - Anggun Lestari; Fadila Casie Musafa; Safa kaila Fitria; Nafis Khairina; Davina Fitri Rahmania; Baidhowi Baidhowi (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study examines the concept of polygamy in the normative framework of Islamic law as stated in the Qur’an and Hadith, comparing it with its practice in modern social reality. Normatively, Islam permits polygamy with a maximum of four wives, under the essential condition that the husband must uphold justice in both material and emotional aspects. In practice, however, polygamy often deviates from this principle of justice, influenced by patriarchal culture, partial religious understanding, and weak legal enforcement. Moreover, the modern implementation of polygamy rarely reflects the example of Prophet Muhammad (peace be upon him), whose marriages were based on humanitarian, social, and da‘wah purposes rather than personal desire. Therefore, the practice of polygamy should be guided by the principles of maqāṣid al-syarī‘ah—justice, welfare, and human dignity. This research concludes that polygamy is not merely a man’s privilege but a heavy moral responsibility, justifiable only when conducted in accordance with the Prophet’s example of fairness and compassion.